Concept of Khiyār in Transaction in Islamic Law - Harun, Daud Rasyid (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2020)
Individuals conducting commercial transactions must carefully weigh-in determining factors prior to sales purchases, either related to goods or pricing. After all, matters are secured, the involved parties can advance with a sales purchase agreement.  Nonetheless, a transaction can typically be canceled post an agreement, due to circumspection on part of the seller or buyer, who is allowed to annul his/her initial plan. Islamic Sharia gives rights to transaction cancellation or activation, and this concept is called “Khiyār”. Various mazhab (Islamic schools of jurisprudence) give consent to Khiyār and its enabling guidelines.  An example is in a case of defective products or discrepancy on the merchant's original product description, etc.  However, depending on the individual situations, all mazhab can either have consensus or disagreement on the nature of Khiyār.  This paper emphasizes the debates due to its relevancy in today’s market, which warrants further development into broader consumer protection.  A qualitative methodology is used for comparison between various mazhab relating to Khiyār based on Fiqh literature. a Khiyār becomes a right for both the seller and buyer.  But, depending on each unique condition, it can also be invalidated.